INTEGRASI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PKN UNTUK MENANAMKAN NILAI IDENTITAS DAN INTEGRASI NASIONAL PADA SISWA SEKOLAH DASAR SDN 1 MANIKYANG - Ni Made Ari Dwijayanti; Dewa Bagus Sanjaya; I Nengah Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Character education plays a crucial role in shaping national awareness and instilling values of identity and national integration in students from an early age. However, its implementation still faces various challenges, such as the lack of parental involvement, limited time due to curriculum demands, and inadequate school resources. These issues have the potential to hinder the effectiveness of character education in the Citizenship Education (PKn) subject. This study aims to analyze effective teaching approaches for instilling identity and national integration values and to identify challenges and solutions in implementing character education at SDN 1 Manikyang. This research employs a qualitative method with a case study approach. The research sample consists of teachers and students at SDN 1 Manikyang, selected using a purposive sampling technique. Data collection techniques include interviews, observations, and document analysis related to the curriculum and character education policies at the school. The data were analyzed using a qualitative descriptive method to understand the patterns and effectiveness of character education implementation in PKn learning. The findings reveal that several effective teaching approaches for instilling identity and national integration values include project-based learning, discussion and reflection methods, and teacher role modeling. The main challenges in implementing character education in this school include a lack of parental involvement, limited time within the curriculum, and insufficient supporting resources. The solutions implemented include increasing parental engagement, integrating character values across various subjects, and optimizing available resources.